Development of Guide Material for the Education of Cultural Immovable Heritage Management for Bachelor Students of Geomatics Engineering - Çoruhlu, Yakup Emre; Er Nas, Sibel; Uzun, Bayram; Yıldız, Okan; Şahin, Fatih; Terzi, Fatih; Çelik, Mehmet Özgür (Geomatics and Environmental Engineering, 2023)
Türkiye has a wealth of foundations and their properties, assets managed by the General Directorate of Foundations (GDF) through its geomatics engineers. This article aims to identify the misconceptions of senior undergraduate geomatics engineering students (sample group) about the relationship between foundations and land ownership registered as cultural heritage. It will develop and implement materials to eliminate these misconceptions and evaluate their effectiveness. This study consists of a preliminary, a pilot and the main application. The data collection instruments are an open-ended questionnaire, a semi-structured interview form and conceptual understanding tests. As a result of the analysis of the pre-study and the pilot study, guidance materials on information deficits and misunderstandings in the application of Article 30 of the Law on Foundations were developed. In the analysis of the quantitative data, the Wilcoxon signed-rank test is used, a non-parametric analysis methods. In the light of the data obtained from the study, it is recommended that materials be developed in other areas of land management to investigate their effectiveness.